Review: PrP 106‐126 – 25 years after. (3rd February 2019) - Forloni, G.; Chiesa, R.; Bugiani, O.; Salmona, M.; Tagliavini, F.
Abstract : A quarter of a century ago, we proposed an innovative approach to study the pathogenesis of prion disease, one of the most intriguing biomedical problems that remains unresolved. The synthesis of a peptide homologous to residues 106‐126 of the human prion protein (PrP106‐126), a sequence present in the PrP amyloid protein of Gerstmann–Sträussler–Scheinker syndrome patients, provided a tractable tool for investigating the mechanisms of neurotoxicity. Together with several other discoveries at the beginning of the 1990s, PrP106‐126 contributed to underpin the role of amyloid in the pathogenesis of protein‐misfolding neurodegenerative disorders. Later, the role of oligomers on one hand and of prion‐like spreading of pathology on the other further clarified mechanisms shared by different neurodegenerative conditions. Our original report on PrP106‐126 neurotoxicity also highlighted a role for programmed cell death in CNS diseases. In this review, we analyse the prion research context in which PrP106‐126 first appeared and the advances in our understanding of prion disease pathogenesis and therapeutic perspectives 25 years later.